Acquired short QT syndrome in a cancer patient treated with Toad. Issue 9 (20th May 2019) - Huang, Yan; Xu, Yong; Barajas‐Martinez, Hector; Hu, Dan
Abstract: Although drug‐induced short QT syndrome (SQTS) has been recognized, we currently report the first acquired SQTS case induced by bufotalinin (toad, an antineoplastic drug), which is a traditional Chinese folk prescription. It has cross reaction with digoxin and affects the Na + ‐K + ‐ATPase, the SR Ca 2+ release from ryanodine receptor‐2 (RyR2), the reactive oxygen species (ROS) production from the mitochondria. The case presented with bradycardia, extreme QT shortening, and sinoatrial block that were resolved after gastric lavage, rehydration, electrolyte (hyperkalemia, hyponatremia, hypocalcemia) correction, and atropine injection. Clinicians should recognize a potential association between toad poisoning and SQTS from this case.